1984
DOI: 10.1111/j.1476-5381.1984.tb10080.x
|View full text |Cite
|
Sign up to set email alerts
|

A 1H n.m.r. study of the role of the glutamate moiety in the binding of methotrexate to Lactobacillus casei dihydrofolate reductase

Abstract: The binding of a series of amide derivatives of methotrexate to Lactobacillus casei dihydrofolate reductase has been studied by inhibition constant measurements and by 1H n.m.r. spectroscopy. Amide modification of the α‐carboxylate of methotrexate was found to prevent interaction of the γ‐carboxylate with the imidazole of His 28. Estimates of the contributions to the binding energy from the α‐carboxylate‐Arg 57 and γ‐carboxylate‐His 28 interactions have been made from a combination of inhibition and n.m.r. dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
5

Year Published

1985
1985
2007
2007

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 22 publications
4
27
0
5
Order By: Relevance
“…For the g-amide MTX complex with DHFR, the 1 H chemical shifts of the His 28 imidazole C2 proton indicated that its pK value is not perturbed from its value in the ligandfree enzyme showing that an ion-pair interaction is not formed (see Figure 17). [116] The 1 H NMR spectrum of the a-amide MTX complex with DHFR also showed that the pK of His 28 was not perturbed even though the g-carboxylate group is available for interaction. Thus, modification of the a-carboxylate not only destroys the Arg 57 interactions, but also perturbs the overall structure such that the available free g-carboxylate can no longer form an ion pair with His 28.…”
Section: Interactions Of His 28 With Carboxylate Groupsmentioning
confidence: 93%
See 4 more Smart Citations
“…For the g-amide MTX complex with DHFR, the 1 H chemical shifts of the His 28 imidazole C2 proton indicated that its pK value is not perturbed from its value in the ligandfree enzyme showing that an ion-pair interaction is not formed (see Figure 17). [116] The 1 H NMR spectrum of the a-amide MTX complex with DHFR also showed that the pK of His 28 was not perturbed even though the g-carboxylate group is available for interaction. Thus, modification of the a-carboxylate not only destroys the Arg 57 interactions, but also perturbs the overall structure such that the available free g-carboxylate can no longer form an ion pair with His 28.…”
Section: Interactions Of His 28 With Carboxylate Groupsmentioning
confidence: 93%
“…These differences in chemical shift are consistent with a change in the orientation of the benzoyl ring, which results in changes in the ring-current shielding effects at neighboring protons. [116,133] …”
Section: Interactions Of His 28 With Carboxylate Groupsmentioning
confidence: 98%
See 3 more Smart Citations